2019
DOI: 10.1101/2019.12.21.885699
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

Intact RNA structurome reveals mRNA structure-mediated regulation of miRNA cleavagein vivo

Abstract: MicroRNA (miRNA)-mediated cleavage is involved in numerous essential cellular pathways. miRNAs recognize target RNAs via sequence complementarity. In addition to complementarity, in vitro and in silico studies have suggested that RNA structure may influence the accessibility of mRNAs to miRNA-Induced Silencing Complexes (miRISCs), thereby affecting RNA silencing. However, the regulatory mechanism of mRNA structure in miRNA cleavage remains elusive. Here, we investigated the role of in vivo RNA secondary struct… Show more

Help me understand this report
View published versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
10
1

Year Published

2020
2020
2024
2024

Publication Types

Select...
5
3

Relationship

3
5

Authors

Journals

citations
Cited by 9 publications
(11 citation statements)
references
References 69 publications
(91 reference statements)
0
10
1
Order By: Relevance
“…This is a stark reminder that the efficacy of any particular amiRNA in vivo remains difficult to predict a priori. We see three explanations for this: (i) even with precise processing, the resulting amiRNAs may not be efficiently loaded into AGO proteins (if there are as yet unknown determinants for miRNA/AGO association, certain amiRNAs may not function well); (ii) it is now well‐established that local mRNA secondary structure at and surrounding miRNA target sites can exert strong effects on miRNA function (Li et al , 2014; Yang et al , 2020) (however, neither the prediction of in vivo local mRNA secondary structures, nor the quantitative details of structure’s effects on miRNA function, are robust enough to make this easily predictable, and, thus, target site selection remains hit or miss); (iii) plant miRNAs can sometimes exert much stronger effects on protein accumulation as opposed to mRNA accumulation (this is often attributed to translational repression occurring independently of mRNA degradation. In our experiments we were not able to assess protein accumulation of our native tomato proteins directly); and (iv) in these experiments, the amiRNAs were expressed transiently through Agrobacterium leaf infiltrations.…”
Section: Discussionmentioning
confidence: 99%
“…This is a stark reminder that the efficacy of any particular amiRNA in vivo remains difficult to predict a priori. We see three explanations for this: (i) even with precise processing, the resulting amiRNAs may not be efficiently loaded into AGO proteins (if there are as yet unknown determinants for miRNA/AGO association, certain amiRNAs may not function well); (ii) it is now well‐established that local mRNA secondary structure at and surrounding miRNA target sites can exert strong effects on miRNA function (Li et al , 2014; Yang et al , 2020) (however, neither the prediction of in vivo local mRNA secondary structures, nor the quantitative details of structure’s effects on miRNA function, are robust enough to make this easily predictable, and, thus, target site selection remains hit or miss); (iii) plant miRNAs can sometimes exert much stronger effects on protein accumulation as opposed to mRNA accumulation (this is often attributed to translational repression occurring independently of mRNA degradation. In our experiments we were not able to assess protein accumulation of our native tomato proteins directly); and (iv) in these experiments, the amiRNAs were expressed transiently through Agrobacterium leaf infiltrations.…”
Section: Discussionmentioning
confidence: 99%
“…MicroRNAs (miRNAs), the single chain of noncoding RNA with 18-25 nucleotides, are characterized by regulating progressions of gene translations via interacting with the 3′untranslated regions (3′-UTRs) of the related messenger RNAs (mRNAs) [9]. MiRNAs take part in the signal transmissions and regulate the life activities of cells such as proliferation, differentiation, and apoptosis [10].…”
Section: Introductionmentioning
confidence: 99%
“…When applying these GC signatures to amiRNAs targeting endogenous or artificial genes, some of the amiRNAs accumulated to higher levels and induced higher target silencing when transiently expressed in Nicotiana tabacum leaves [60]. In another recent work, it was suggested that in vivo mRNA structure regulates miRNA cleavage in Arabidopsis [61]. In particular, the single-strandedness of the two nucleotides immediately downstream of the miRNA target site, named Target Adjacent structure Motif (TAM), seems to favor miRNA cleavage [61].…”
Section: Othermentioning
confidence: 99%
“…In another recent work, it was suggested that in vivo mRNA structure regulates miRNA cleavage in Arabidopsis [61]. In particular, the single-strandedness of the two nucleotides immediately downstream of the miRNA target site, named Target Adjacent structure Motif (TAM), seems to favor miRNA cleavage [61]. It is tempting to speculate that art-sRNAs targeting viral target sites with TAMs may have an increased cleavage activity and, subsequently, an enhanced antiviral activity.…”
Section: Othermentioning
confidence: 99%